Stress-strength reliability: a quantile approach. Issue 1 (2nd January 2022) - Mathew, Angel; Deepa, K. R.
Abstract : In reliability modelling and analysis of systems, quantile functions play a significant role when the distribution function under consideration does not possess an analytically tractable form, though the corresponding quantile function has an explicit form. In the present paper, we propose a quantile-based approach for stress-strength reliability of a system. We also introduce the quantile versions of stress-strength reliability for residual lifetime random variables. The effect of monotone transformations and some characterizations of the proposed measures are discussed. The reliability of multi-component stress-strength systems based on quantiles is also considered.